Recensement 1891 : comtš de Madawaska et de Victoria, province du Nouveau-Brunswick = 1901 census : Madawaska and Victoria Counties, Province of New Brunswick - Poitras, Jean-Guy 1949- (Edmunston, NB Jean-Guy Poitras, 1996)
Donated, 10/98
Keywords: Registers of birth, etc. -- New Brunswick -- Madawaska (County); Registers of birth, etc. -- New Brunswick -- Victoria (County); Madawaska (N.B. : County) -- Genealogy; Madawaska (N.B. : County) -- Census, 1891; Victoria (N.B. : County) -- Census, 1891